Proceedings Ninth Annual IEEE International Conference and Workshop on the Engineering of Computer-Based Systems
DOI: 10.1109/ecbs.2002.999829
|View full text |Cite
|
Sign up to set email alerts
|

On the relation between design contracts and errors: a software development strategy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Briand et al have studied the impact of contracts for testability of object-oriented systems in [25]. Nordby et al [5] have proposed a development methodology based on contracts and showed that it speeds up the testing and integration phases. Other works have focused on contracts as a means for testing [37], [38] or proving [39].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Briand et al have studied the impact of contracts for testability of object-oriented systems in [25]. Nordby et al [5] have proposed a development methodology based on contracts and showed that it speeds up the testing and integration phases. Other works have focused on contracts as a means for testing [37], [38] or proving [39].…”
Section: Related Workmentioning
confidence: 99%
“…In [5], Nordby et al propose a methodology to use contracts in the different phases of the development process. They distinguish two types of contracts: weak and strong.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, DbC contributes to less time spent on writing tests [29]. Blom et al [7] presented a DbC-based development strategy and a case study applying it to an enterprise project. They found that the approach resulted in fewer errors and decreased development time.…”
Section: Related Workmentioning
confidence: 99%